612 Human CLEC9A antibodies deliver NY-ESO-1 antigen to CD141+ dendritic cells to activate naïve and memory NY-ESO-1-specific CD8+ T cells. (9th November 2020) - Masterman, Kelly-Anne; Haigh, Oscar; Tullett, Kirsteen; Leal-Rojas, Ingrid; Walpole, Carina; Pearson, Frances; Cebon, Jonathon; Schmidt, Christopher; O'Brien, Liam; Rosendahl, Nikita; Daraj, Ghazal; Caminschi, Irina; et al.
Abstract : Background: Dendritic cells (DC) are crucial for the efficacy of cancer vaccines, but current vaccines do not harness the key cDC1 subtype required for effective CD8+ T cell mediated tumor immune responses. Vaccine immunogenicity could be enhanced by specific delivery of immunogenic tumor antigens to CD141+ DC, the human cDC1 equivalent. CD141+ DC exclusively express the C-type-lectin-like receptor CLEC9A, which is important for the regulation of CD8+ T cell responses. This study developed a new vaccine that harnesses a human anti-CLEC9A antibody to specifically deliver the immunogenic tumor antigen, NY-ESO-1 to human CD141+ DC. The ability of the CLEC9A-NY-ESO-1 antibody to activate NY-ESO-1 specific naïve and memory CD8+ T cells was examined and compared to a vaccine comprised of a human DEC-205-NY-ESO-1 antibody that targets all human DC. Methods: Human anti-CLEC9A, anti-DEC-205 and isotype control IgG4 antibodies were genetically fused to NY-ESO-1 polypeptide. Cross-presentation to NY-ESO-1- epitope specific CD8+ T cells and reactivity of T cell responses in melanoma patients was assessed by IFNγ production following incubation of CD141+ DC and patient peripheral blood mononuclear cells with targeting antibodies. Humanized mice containing human DC subsets and a repertoire of naïve NY-ESO-1-specific CD8+ T cells were used to investigate naïve T cell priming. T cell effector function was measured by expression of IFNγ, MIP-1β, TNF and CD107a and by lysis of target tumor cells. Results: CLEC9A-NY-ESO-1 Ab were effective at mediating delivery and cross-presentation of multiple NY-ESO-1 epitopes by CD141+ DC for activation of NY-ESO-1-specific CD8+ T cells. When benchmarked to NY-ESO-1 conjugated to an untargeted control antibody or to anti-human DEC-205, CLEC9A-NY-ESO-1 was superior at ex vivo reactivation of NY-ESO-1-specific T cell responses in melanoma patients. Moreover, CLEC9A-NY-ESO-1 induced priming of naïve NY-ESO-1-specific CD8+ T cells with polyclonal effector function and potent tumor killing capacity in vitro. Conclusions: These data advocate human CLEC9A-NY-ESO-1 antibody as an attractive strategy for specific targeting of CD141+ DC to enhance tumour immunogenicity in NY-ESO-1-expressing malignancies. Ethics Approval: Written informed consent was obtained for human sample acquisition in line with standards established by the Declaration of Helsinki. Study approval was granted by the Mater Human Research Ethics Committee (HREC13/MHS/83 and HREC13/MHS/86) and The U.S. Army Medical Research and Materiel Command (USAMRMC) Office of Research Protections, Human Research Protection Office (HRPO; A-18738.1, A-18738.2, A-18738.3). All animal experiments were approved by the University of Queensland Animal Ethics Committee and conducted in accordance with the Australian Code for the Care and Use of Animals for Scientific Purposes in addition to the laws of the United States and regulations of the Department of Agriculture.